2006
DOI: 10.1080/00952990500328539
|View full text |Cite
|
Sign up to set email alerts
|

Risk for Marijuana-Related Problems among College Students: An Application of Zero-Inflated Negative Binomial Regression

Abstract: Results generally are consistent with theories of the differential association of social-environmental and biopsychological variables with use and problems, respectively. Zero-inflated regression models are a useful strategy to examine risk behaviors with low base rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 26 publications
2
50
1
Order By: Relevance
“…Such a model allows zeroes to be accounted for by the binomial distribution and by the count distribution, thus allowing the model to fit the higher occurrence of zeroes in our outcome variables. The zero-inflated negative binomial model has been useful in predicting low base-rate phenomena in other studies (20,21). A Vuong test (17) indicated that the zero-inflated negative binomial model fit better than the negative binomial model.…”
Section: Methodsmentioning
confidence: 99%
“…Such a model allows zeroes to be accounted for by the binomial distribution and by the count distribution, thus allowing the model to fit the higher occurrence of zeroes in our outcome variables. The zero-inflated negative binomial model has been useful in predicting low base-rate phenomena in other studies (20,21). A Vuong test (17) indicated that the zero-inflated negative binomial model fit better than the negative binomial model.…”
Section: Methodsmentioning
confidence: 99%
“…For all variables the distributions were positively skewed, approximating a negative binomial distribution with the exception of a disproportionately large number of zero values. Thus, zero-infl ated negative binomial (ZINB) regression was selected as the primary analysis strategy (Atkins and Gallop, 2007;Heilbron, 1994;Hilbe, 2007;Simons et al, 2006). ZINB regression is a type of mixture model in which a negative binomial regression is fi t and excess zeros (i.e., over and above what is predicted by the negative binomial regression) are modeled using a logistic regression.…”
Section: Discussionmentioning
confidence: 99%
“…ZIP regression is appropriate for modeling count data with excessive zeros (Muthén & Muthén, 1998-2006. A large positive Vuong test for nonnested models favored the use of a ZIP model over an ordinary Poisson regression, z = 6.79, p < .0001.…”
Section: Data Analysis Planmentioning
confidence: 99%
“…A large positive Vuong test for nonnested models favored the use of a ZIP model over an ordinary Poisson regression, z = 6.79, p < .0001. Maximum likelihood estimation with robust standard errors using a Monte Carlo numerical integration algorithm was employed for this analysis (for details see Muthén, 2004;Muthén & Muthén, 1998-2006. With a ZIP model, two regressions are simultaneously estimated.…”
Section: Data Analysis Planmentioning
confidence: 99%
See 1 more Smart Citation